Tectonic evolution of the Southern Austral-Magallanes Basin in Tierra Del Fuego (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The evolutionary history of the Austral Magallanes has been object of several studies both in Chile and Argentina, due to its importance as hydrocarbon and gas producer. In the evolution of southern South America, a stage of intracratonic rifting development between the Middle-Late Jurassic has been recognized in a wide part of southern Patagonia that generated an extensional basin (Rocas Verdes basin). Following the creation of a synrift fault system the basins evolved towards an Early Cretaceous postrift sag stage that deposits a thick pelitic succession in a marine shelf environment, constituting these deposits in the main reservoir and source rock for the oil plays. During the middle-Late Cretaceous in the entire Austral Patagonian region took a place a compressional regime over the east and south margin of southernmost South America. Product of Andean growth in this sector were produced a magmatic arc, a Basement domain and fold-and-thrust belt, and a foreland basin related to flexural loading. Since the Neogene to Recent, the Fueguian Andes were affected by transpressive tectonics related to the opening of the Drake Passage. This contribution is a review, and pretend to account the stratigraphic and the structural evolution of the basin of the southernmost Patagonia and its fold-and-thrust belt associated, summarized in a regional stratigraphic correlations for Late Jurassic–Quaternary rock units throughout the southern Austral-Magallanes basin. However, new ideas and interpretation are presented supported by new information at the regional level, using a north-to-south direction seismic-line reflection, well-log data and their regional correlation. The tectonic evolution of the studied depocenters is related to structural phases recognized in the Patagonian-Fueguian Andes and the Burdwood bank, constituting their southern active boundary. These depocenters migrated to the east in the southern Patagonian Andes and towards the north and east in Tierra del Fuego and Malvinas. The thrust advance is evidenced by discordances within the basin fill that coalesce towards the external depocenter and depositional bulge, characteristic geometric stacking patterns and configuration of clinoforms. These key surfaces enabled the definition of four evolutionary stages: Foreland I (Coniacian (?) - Maastrichtian), Foreland II (early-middle Paleocene – middle Eocene), Foreland III (early-middle Eocene - Oligocene) and Foreland IV (early Miocene - Pliocene).